1997
DOI: 10.1136/bjo.81.8.654
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of optic nerve head drusen with the scanning laser ophthalmoscope

Abstract: Background-Optic nerve head drusen may present diagnostic diYculties in cases of disc swelling. Imaging of the nerve in a search for drusen is often inconclusive, especially in children, where drusen may be buried below the surface of the nerve head. Methods-A small study was carried out using a scanning laser ophthalmoscope (SLO) with an infrared confocal facility to scan deep within optic discs in an attempt to image drusen. Results-The SLO was able to demonstrate superficial and buried drusen (using the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 7 publications
1
14
0
1
Order By: Relevance
“…3 Other methods including autofluorescence and staining during the late phases of fundus fluorescein angiography, cranial computerized tomography, magnetic resonance imaging, ultrasonography and scanning laser ophthalmoscopy have been proposed to confirm diagnosis. [4][5][6] The pathogenesis of drusen formation still remains obscure, however a relationship between the axonal degeneration and abnormal axoplasmic flow in the retinal nerve fibers has been suggested. 7,8 RNFL evaluation in patients with ONHD is required since the patients with ONHD may have visual field defects that resemble glaucoma and the interpretation of the optic nerve head may be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…3 Other methods including autofluorescence and staining during the late phases of fundus fluorescein angiography, cranial computerized tomography, magnetic resonance imaging, ultrasonography and scanning laser ophthalmoscopy have been proposed to confirm diagnosis. [4][5][6] The pathogenesis of drusen formation still remains obscure, however a relationship between the axonal degeneration and abnormal axoplasmic flow in the retinal nerve fibers has been suggested. 7,8 RNFL evaluation in patients with ONHD is required since the patients with ONHD may have visual field defects that resemble glaucoma and the interpretation of the optic nerve head may be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…12 Retinitis pigmentoza, anjioid streaks, psödoksan-toma elastikum ve Alagille sendromu gibi kalı-tımsal geçişli hastalıklarla sık görüldüğü bildirilmiştir. 12,13 Oftalmoskopik muayenede görülebilen drusen "belirgin drusen" olarak adlandırılırken, olgumuzda olduğu gibi bulanık disk kenarları ve damarların anormal dallanması ile kendini göste-ren fakat görülemeyenler "gömülü drusen" olarak adlandırılmaktadır. Optik disk druseni erken yaş-larda disk yüzeyinin altında bulunduğundan oftalmoskop ile görülemez.…”
Section: Discussionunclassified
“…Longer wavelengths such as near infrared 830 nm are useful for indocyanine angiography,19 choroidal abnormalities such as naevi,20 imaging through lens opacities,21macular oedema and holes,22 and drusen 2324Freeman et al  25 reported simultaneous indocyanine green and fluorescein angiography using a confocal scanning laser ophthalmoscope.…”
Section: Multispectral Imagingmentioning
confidence: 99%